O2 Gas Generating Prototype In Public Transportation - Anggara Trisna Nugraha; Rahman Arifuddin (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
Air is a layer of gas that covers the Earth. Clean air is air that is free of impurities or substances that can poison the body and is commonly found in areas where there are many plants. The realization is done through a combination of the TGS 2442 sensor on the detector with a high voltage system on the T-Box. The TGS2442 sensor is a high sensitivity sensor to carbon monoxide gas. Thus, the resulting carbon monoxide gas exhaust that has gone through the process will produce oxygen gas because the steel plate on the T-Box functions as a carbon binder. The amount of smoke, which is the output form, is already in the form of ppm, which can be found using the display on the serial monitor and by calibrating using a gas analyzer. The gas analyzer is in the lowest range, namely 100ppm, the sensor detects 116ppm with a percent error of 16%. And when the gas analyzer is in the highest range of 600ppm, the sensor detects 603ppm with an error of 0.5%.